Cloning and sequencing of complementary DNAs encoding the alpha-subunit of translational initiation factor eIF-2. Characterization of the protein and its messenger RNA. - H Ernst; Roger F. Duncan; J W Hershey (1987)
A clone encoding the a-subunit of eukaryotic initiation factor 2 (eIF-2a) was isolated from a Xgtl l expression library of rat brain cDNAs.The fusion protein expressed by the recombinant phage reacts with eIF-2a antiserum except when the serum is preadsorbed with pure eIF-2.The translation of hybrid-selected HeLa cell mRNA produces two proteins which are indistinguishable from authentic HeLa eIF-2a and its phosphorylated form when analyzed by electrophoresis in two-dimensional isoelectrofocusing/sodium dodecyl sulfate-polyacrylamide gels and by partial protease digestion.HeLa cell eIF-2a mRNA migrates as a single band of about 1600 nucleotides.The rat cDNA insert was sequenced, and the region coding for eIF-2a was identified.A human cDNA clone was obtained by hybridization screening with the rat cDNA, and its sequence was determined also.Both rat and human eIF-2a proteins comprise 315 amino acids (36.1 kDa) and differ by only three amino acids.The eIF-2a mRNA is found exclusively in polysomes containing 10 or more ribosomes in exponentially growing HeLa cells.In serum-depleted cells which synthesize eIF-2 and bulk protein more slowly than exponential cells, the level of eIF-2a mRNA is not changed, the average polysome size is reduced to 7, and little or no eIF-2a mRNA is detected in the ribonucleoprotein fraction.These results are consistent with the view that eIF-2a mRNA translation is very efficient compared to other mRNAs in the cell.Initiation of protein synthesis in mammalian cells is mediated by a complex array of proteins called initiation factors.One of the initiation factors, eIF-2,' forms a ternary complex with methionyl-tRNAi and GTP and promotes the binding of the initiator tRNA to 40 S ribosomal subunits (1-3).eIF-2 comprises three nonidentical subunits, a (36 kDa), p (38 kDa), and y (52 kDa).In hemin-deprived rabbit reticulocyte lysates, inhibition of protein synthesis is due to the phosphorylation